Giving Red Ginger Water and Green Coconut Water to Reduce Menstrual Pain in Adolescent Girls (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2023)
Dysmenorrhea is menstrual pain that is felt before or during menstruation and is usually cramping. In Indonesia, the incidence of dysmenorrhea is around 55% and in West Java it is 54.9%. Nonpharmacological pain management can be done by giving red ginger and green coconut water. Quasi-experiment research design with two group pretest-posttes research design. Aiming to determine the effect of giving red ginger water and young coconut water on reducing menstrual pain in adolescent girls Data were analyzed using paired and independent tests. There is an effect of giving red ginger water and green coconut water on reducing menstrual pain in adolescent girls with a P value of 0.00 (<0.05).There is a significant difference between the effect of red ginger water and green coconut water on reducing pain from a p value of 0.02 <? (0.05). Red ginger water and green coconut water have an effect on reducing menstrual pain in adolescent girls.